Elevated MFG-E8 in CSF in the Early Stage Indicates Rapid Recovery of Mild Aneurysmal SAH Patients. (11th October 2022) - Pang, Cong; Peng, Zheng; Li, Xiaojian; Gao, Yongyue; Liu, Xunzhi; Wang, Han; Lu, Yue; Zhuang, Zong; Zhang, Qingrong; Li, Wei; Hang, Chunhua
Abstract : Background . Aneurysmal subarachnoid hemorrhage (aSAH) can impair blood perfusion in brain tissue and cause adverse effects. Microglia, which are the inherent immune cells of the brain, significantly activate and play a role in phagocytosis, anti-inflammatory, proinflammatory, and damage repair in this process. Milk fat globule epidermal growth factor 8 (MFG-E8) is the bridging molecule of this process and mediates the activation and biological effects of microglia. Methods . We obtained cerebrospinal fluid (CSF) from patients with aSAH at various times (the third day, seventh day, and ninth day) as well as from patients in the control cohort. MFG-E8 protein levels in CSF were measured by enzyme-linked immunosorbent assay (ELISA). Meanwhile, we evaluated the GCS and GOS of aSAH patients on admission and on the third day, seventh day, ninth day, and at discharge. Then, we analyzed the association between the levels of MFG-E8 and the changes in GCS and GOS. Results . MFG-E8 expression rose in the early stage on the third day and reached equilibrium around day 7 and day 9. The levels of MFG-E8 on the third day were associated with the change in GOS on the seventh day (r = 0.644, p = 0.018 ) and ninth day (r = 0.572, p = 0.041 ) compared with admission but were not correlated with the change on day 3 or at discharge. The levels of MFG-E8 were not correlated with any change in GCS. Conclusions . We found that aSAH resulted in an upregulation of MFG-E8 in CSF. Moreover, high MFG-E8 levels in the early stage indicated a rapid recovery of mild aSAH patients.